Program Edukasi Pembelajaran Kecerdasan Buatan untuk Meningkatkan Literasi dan Kemampuan Berpikir Kritis Siswa SMK N 1 Cipeundeuy - Wahyudin, Asep; Piantari, Erna; Junaeti, Enjun; Anisyah, Ani (EDUPEDIA Publisher, 2024)
Critical thinking skills are one of the 21st century skills needed to prepare the younger generation in the era of society 5.0. Therefore, education should be designed not only to improve knowledge and skills but also critical thinking skills. In addition, of course, critical thinking skills need to be supported by mastery of the latest knowledge, one of which is knowledge of digital technology based on artificial intelligence. Vocational schools or vocational schools are educational institutions that focus on preparing students to be ready to work. By including an artificial intelligence curriculum designed with a form of learning that can improve critical thinking skills, vocational school graduates have greater potential in producing a generation that is ready to work and compete in the era of social 5.0. Therefore, this program is designed as an initiation of artificial intelligence technology education for vocational school students who focus on developing solutions in the form of artificial intelligence-based technology products